STRATEGI KOMUNIKASI KETUA LAZISNU MWCNU PESANGGARAN DALAM MENINGKATKAN MOTIVASI KERJA ANGGOTA - Moh. Muslimin (JDARISCOMB:Jurnal Komunikasi dan Penyiaran Islam, 2022)
An organization always strives to create a harmonious working relationship between leaders and members, to maintain these conditions a leader is needed who can have a great influence and can motivate members to work, in order to optimize their performance. An effective leader must be able to provide direction, evaluation, and correction of the efforts made by members in achieving organizational goals. The focus of this research is on "How the Communication Strategy of the chairman of Lazisnu MWCNU Pesanggaran in Increasing the Work Motivation of Members" This study aims to find out how the communication strategy and relationships that occur in LazisNu MWCNU Pesanggaran. The method used in this study is a qualitative method, data obtained by means of observation, interviews and documentation. The data sources used are primary data sources and secondary data sources. And there are 3 stages of data analysis techniques, namely data reduction, data processing and presentation. The results of this study indicate that the communication strategy used by LazisNu MWCNU Pesanggaran is a chain, wheel, circle, and star pattern, these four have the same focus, namely a leader, how the leader's relationship with members so as to create a good response and reciprocity so that instructions delivered can be executed properly.